The religious reforms of Sheikh Mahmoud Shaltout, addressed to the Society for Rapprochement between Islamic Schools of thought (1963-1958), a historical study (Journal of the College of Basic Education, 2024)
The subject of rapprochement between religious sects is one of the most important topics and studies that many researchers turn away from. Shedding light on this subject and the role of close associates, especially Sheikh Mahmoud Shaltut, who had a prominent role in this field, is very important in order to achieve and strengthen ties between sects. Islam by understanding the differences contained therein and removing their negative effects and not removing the root of the difference in order to get rid of the mutual enmity between the Islamic sects and bring the points of view closer. Achieving the lofty goal.